ISOLATION AND CHARACTERIZATION OF SECONDARY METABOLITES FROM THE ROOT CULTURES OF MORUS SHALUN (MORACEAE) - FITRIANI (NIM: 20515035), RIZKI
Plants have been known for thousands years to have an important role for human as the source of the primary needs as well as for traditional medicines. Phytochemical and bioactivity studies of the secondary metabolites from the plants has been widely conducted on account of utilization of plants for healing and disease treatment. One genus of plants that is potential to be investigated is Morus of Moraceae family. Phytocemical studies showed that Morus plants produce either phenolic compounds, mainly stilbenes, 2-arylbenzofurans, flavonoids, and Diels-Alder adducts, or non phenolic compounds, such as terpenoids and steroids. Some of these secondary metabolites have shown important and various bioactivity, such as antitumor, antioxidant, antimicrobial, anti-inflammatory, and antiviral. The presence of bioactive secondary metabolites is very potential to be used as lead compound as a part of efforts in drug discovery. The source of bioactive compounds not only can be obtained from the plants but also from the plant tissue cultures. Plant tissue cultures technique is an advanced biotechnology method in natural product chemistry research as an alternative supply for the production of biologically important secondary metabolites. Therefore, the isolation and characterization of secondary metabolites from Morus shalun root cultures were implemented in this research. This is the first study to obtain information of the secondary metabolites in the root cultures of Morus shalun. Root cultures were grown in liquid MS (Murashige-Skoog) media with the addition of hormone IBA (indole-3-butiric acid) 1 ppm. Root cultures were subcultured for propagation at age of 4 or 5 weeks. Then, 8 weeks old root cultures were harvested when the production of secondary metabolites was expected to reach the maximum yield. Isolation was carried out both on the root cultures and the liquid media. The liquid media (+- 7 L) was extracted with ethyl acetate (EtOAc). The organic phase was evaporated with low pressure to get dry EtOAc extract weighing 4.2 g. The root cultures of M. shalun (144 g) was macerated with methanol and evaporated to obtain dry methanol extract weighing 22 g. Each extract was fractionated and purified by using various chromatographic techniques, such as vacuum liquid chromatography, gravity column chromatography, and radial chromatography. Six compounds have been isolated from the liquid media, i.e. M4 (5 mg), M5 (11 mg), M6 (6 mg), M7 (9 mg), M8 (8 mg), and Mx (3 mg). Five compounds have been characterized, i.e M4, M5, M6, M7, and M8. Three of them, i.e M5 (2), M7 (4), and M8 (5) are new Diels-Alder type adducts, while M6 is a known Diels-Alder type adduct, mulberofuran K (3). Three compounds have been isolated from the root cultures of M. shalun, i.e A1 (7 mg), A2 (1,5 mg), and A3 (3 mg). A1 has been characterized and is identified as moracin M (6). The molecular structures of the isolated compounds were determined based on spectroscopic data, including 1D-NMR (1H and 13C), 2DNMR (HSQC and HMBC), and high resolution mass spectra. The new compounds, M5 (2), M7 (4), and M8 (5), have cytotoxicity against murine leukimia P-388 cells with IC50 0,7; 0,7; and 2,0 μg/mL, respectively, while compounds M4 (1), mulberrofuran K (3), and moracin M (6) have been reported to possess cytotoxicity against murine leukemia P-388 cells with IC50 1,8; 1,9; and 2,6 μg/mL, respectively. All the compounds isolated both from the liquid media and the root cultures of M. shalun are potential as the lead compounds for anticancer agent.